Quantification of the Transparency of the Transparent Soil in Geotechnical Modeling. (9th September 2018) - Yi, Li-Da; Lv, Hua-Bin; Ye, Tian; Zhang, Yi-Ping
Abstract : An indispensable process of geotechnical modeling with transparent soils involves capturing and analyzing images, in which favorable transparency is required for optical measurements. This paper proposes an objective framework for quantification of transparency in transparent soil based on its transmittance. Specifically, transparent soil with fused quartz serves as the soil sample for the detection of transmittance, and transmittance's impact on imaging quality in geotechnical modeling with transparent soil is investigated through an evaluation function of image clarity. According to the results of research about transparent soil with fused quartz, viewing depth and refractive index matching are the dominant factors that affect variations in transmittance of transparent soil, and the variations of transmittance are subjected to exponential decay regarding viewing depth or refractive index matching based on the theoretical modeling's function of curve fitting. Moreover, experimental results indicate that imaging quality of geotechnical modeling with transparent soil is enhanced with increasing transmittance, and imaging quality shows a remarkable improvement when transmittance is greater than 90%.